2004
DOI: 10.1038/sj.gene.6364133
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β polymorphisms in Colombian patients with autoimmune rheumatic diseases

Abstract: Interleukin-1 beta (IL-1b) exerts a range of inflammatory and immunomodulatory activities that are important in host defense and autoimmune response. The IL-1b gene, located on chromosome 2 (2q13), is polymorphic. The influence of its polymorphism on 355 patients with autoimmune rheumatic diseases was examined. To this effect, 172 patients with rheumatoid arthritis (RA), 114 with systemic lupus erythematosus (SLE), and 69 with primary Sjö gren's syndrome (pSS) were studied. The control group consisted of 392 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 37 publications
3
58
2
4
Order By: Relevance
“…Their clinical and immunological characteristics were systematically recorded as previously reported. 13,14 The study included 263 women and 35 men with RA, 15 their mean age7s.d. was 48.5714.2 years, the mean duration of disease was 1178.1 years, and 80% tested positive for RF.…”
Section: Resultsmentioning
confidence: 99%
“…Their clinical and immunological characteristics were systematically recorded as previously reported. 13,14 The study included 263 women and 35 men with RA, 15 their mean age7s.d. was 48.5714.2 years, the mean duration of disease was 1178.1 years, and 80% tested positive for RF.…”
Section: Resultsmentioning
confidence: 99%
“…The protective haplotypes of the HLA complex genes have been shown in several autoimmune diseases like diabetes, rheumatoid arthritis and systemic lupus erythematosus. [48][49][50] Similarly, certain HLA haplotypes have been shown to be protective in psoriasis. [51][52][53] The knowledge about the non-MHC protective genes in psoriasis is insufficient at the present time.…”
Section: Discussionmentioning
confidence: 99%
“…Different results were reported on the effect of IL1B (+3953) allele on IL-1β protein production. Some studies showed that an association was seen between IL1B (+3953) and increased plasma levels of IL-1β 9,30 , but others found no affect on IL-1 levels [33][34][35] . No studies are available on the relationship between CAD and polymorphism in the IL1B gene (+3953).…”
Section: Discussionmentioning
confidence: 99%